REFINED ESTIMATE AND RESEARCHES OF STRAIN-STRESS STATE OF BEAM DURING BEND - Luchko, Y. Y.; Dobryanskiy, I. M. (Science and Transport Progress, 2010)
In the paper it is presented a solution for the problem of elasticity theory about the beam bending, which is being constructed with account of available finite base areas taking up a temporary load in the district of beam edge, where the cracks can initiate and propagate.